Analisis Knowledge Management Menggunakan Model Big Data di Media Sosial UMKM - Prima Yulianti; Rahmi Fahmy; Hafiz Rahman; Harif Amali Rivai (Jurnal Manajemen Informatika JAMIKA, 2023)
Social media overcomes the limitations of technology and knowledge management. Previous generations of knowledge management were very rigid, often leaving companies stuck and overly reliant on outdated or obsolete knowledge. Lack of skills in the use of social media, lack of awareness of the value of knowledge management, availability of time to invest both in the acquisition of digital skills as well as in the creation and duration of content, creates perceived barriers to social media uptake. Through a concise and relevant knowledge management process, and utilizing the use of social media, MSMEs can display and communicate messages, products or services, images, and most importantly uniqueness which is their selling point. The purpose of this study is to conceptualize the use of social media in an effort to improve the performance of MSMEs in terms of the perspective of knowledge management-based human resource management with the model of big data for SME approach. The method used is a relevant literature review from 2018 to 2022. The results show that the importance of using social media and knowledge management through big data has a synergistic relationship. Shows that the use of strategic data, representation of knowledge-guided business planning, is a solution for MSMEs in implementing technology through the construction of new knowledge as a tool to encourage innovation and productivity in order to increase business competitiveness and its impact on MSME performance.